2007
DOI: 10.1097/01.ccm.0000257464.79067.af
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-induced endothelial oxidative stress is related to the severity of septic shock*

Abstract: Plasma from septic shock patients induces ROS formation by naive HUVEC, and the extent of ROS formation correlates with mortality and with criteria of the severity of septic shock as SOFA score and SAPS II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 33 publications
6
40
1
5
Order By: Relevance
“…We demonstrated that these patients had a marked OS and a downregulation of monocyte HLA-DR antigen expression, findings confirmed in previous studies [6,8,9] .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We demonstrated that these patients had a marked OS and a downregulation of monocyte HLA-DR antigen expression, findings confirmed in previous studies [6,8,9] .…”
Section: Discussionsupporting
confidence: 79%
“…Current knowledge concerning the role of OS and HLA-DR expression in sepsis remains unresolved. Although some studies found a correlation between OS and outcome [8,21] , these results are contested by others. Perianayagam et al [22] evaluated a cohort of 200 patients with AKI and found that the incidence of sepsis was not significantly different according to the various levels of NADPH oxidase, another OS marker.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…These results, therefore, demonstrate that increased oxidative stress is a marker of increased risk of death; this finding supports previous similar findings of other researchers. [31,32] Contrary to the hypothesis, no significant correlation was found between E-selectin and TBARS. The lack of correlation could be a consequence of the effect of increased oxidative damage to the endothelial cells, a factor known to negatively affect E-selectin expression.…”
Section: Discussioncontrasting
confidence: 51%
“…Investigators have demonstrated that while TAC between septic patients and healthy volunteers are similar, TAC levels decline over time in the septic patients suggesting a loss in the ability of septic patients to scavenge the ROS. In vitro studies in which human umbilical vein endothelial cells are treated with plasma from patients with septic shock have demonstrated that high amounts of ROS are produced [1] and intracellular glutathione stores, the most abundant antioxidant, are depleted [2]. The amount of ROS produced correlated to the severity of illness and pretreatment with n-acetylcysteine or glutathione decreased ROS production and cell death [2].…”
Section: Oxidative Stress In Sepsismentioning
confidence: 99%